PENGARUH BAURAN PEMASARAN (MARKETING MIX) TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN PADA RESTO CAFE ROEMAH NENEK - Mayranti Nur Azma Azhar, - (2009)
This research has a purpose to identify the impact of marketing mix (product, price, promotion and place) toward consumer buying decision at Resto Café Roemah Nenek. The research methods applied in this research are descriptive method and verification. Samples are chosen using accidental random sampling method by involving as much as 150 consumers of Resto Café Roemah Nenek as respondents. Data analysis technique in this research is multiple linear regressions. The result of this research proves that marketing mix are positive towards consumer buying decision as much as 65,6%, on the other hand the other 34,4% is influenced by other factors which aren't investigated by the author. As a result, it is needed to make an improvement on marketing mix by improving product quality, adjusting price with consumer buying power, increasing the promotion frequency, and providing an enhanced comfy place so that consumer will make a buying decision on Resto Café Roemah Nenek.